Imperium [videorecording (DVD)] - German, Mike, 1963- (2016)
Inspired by real events. When a radical white supremacy terrorist group steals toxic materials in order to build a dirty bomb, FBI Agent Nate Foster goes undercover in order to infiltrate their shadowy underworld. But can Nate find the group's leader and the bomb before his cover is blown?